2017
DOI: 10.1103/physreve.95.053113
|View full text |Cite
|
Sign up to set email alerts
|

Experimental velocity study of non-Boussinesq Rayleigh-Bénard convection

Abstract: The effects of strongly varying fluid properties, beyond the validity range of the so-called Boussinesq approximation, were experimentally studied in Rayleigh-Bénard (RB) convection. Two experiments were conducted in the same cubical RB convection cell at similar Rayleigh and Prandtl numbers. In one experiment water was used as working fluid and the imposed temperature difference between the top and bottom plates of the cell was such to ensure non-Boussinesq conditions. In the other experiment, taken as a refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We use the correlation µ(cP) = 0.02141 × 10 247.8/(T (K)−140) ∼ 0.3654 [25]. The Boussinesq approximation originally expresses that (i ) density fluctuations result principally from thermal effects-analogous to dissolution here-rather than pressure effects, and (ii ) density variations are neglected except when they are coupled to gravity (i.e., in the buoyancy force, −ρ g) [38,39]. Under this approximation, density variations are small compared to velocity gradients and a divergence-free flow (∇ · v = 0) can be assumed.…”
Section: Formulationmentioning
confidence: 99%
“…We use the correlation µ(cP) = 0.02141 × 10 247.8/(T (K)−140) ∼ 0.3654 [25]. The Boussinesq approximation originally expresses that (i ) density fluctuations result principally from thermal effects-analogous to dissolution here-rather than pressure effects, and (ii ) density variations are neglected except when they are coupled to gravity (i.e., in the buoyancy force, −ρ g) [38,39]. Under this approximation, density variations are small compared to velocity gradients and a divergence-free flow (∇ · v = 0) can be assumed.…”
Section: Formulationmentioning
confidence: 99%
“…(i) The characteristic velocity becomes asymmetric, as found in previous numerical [13,16,17] and experimental studies [25,26], and (ii) the shape of the velocity and temperature profiles inside the boundary layers changes due to temperature-dependent fluid properties.…”
Section: A Derivationmentioning
confidence: 56%
“…This is nontrivial and has so far not been done experimentally because Pr m andX are both intrinsic properties of a fluid. Previous experiments and simulations have been conducted at fixed T m with varyingX by changing and P m , thus causing also changes in Ra m and Pr m [11,14,17,19,25,26]. Manipulating the degree of the NOB effect in such a way always results also in a change of Ra m , which also changes the heat flux.…”
Section: Experimental Program and The Description Of The Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…For liquid working fluid cases, having large temperature differences between hot and cold surfaces and its effect on the viscosity along with applying the Boussinesq approximation for non‐gaseous mixtures may result in inaccurate results. For instance, Valori et al 25 used water and methanol as their working fluid beyond the validity of the Boussinesq approximation in a cubical Rayleigh‐Bénard convection cell. They found that the non‐Boussinesq effect manifests itself as an increase of time‐averaged horizontal velocity component close to the bottom wall of the cell and as a global top‐bottom asymmetry of the velocity field.…”
Section: Introductionmentioning
confidence: 99%